Poli-2-vinilfuran'ın organik reaksiyonları - Küsefoğlu, Selim. (Thesis (Assoc. Prof.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1980., 1980)
The known and varied organic chemistry o f the furan ring has been used t o successfully transform poly-2-vinyl furan (PZVF) to a number of new polymeric systems. The Diels Alder adduct o f P2VF with maleicanhidride (3), the cross linking product of P2VF with asetone (7); the 2 - 4 dinitroph,enylhydrazine derivative of the acid hydrolysis product of P2VF (6) and the 5-aldehyde (8), 5-bromide (9) and 5-sulfonat (10) derivatives of P2VF have been synthesized and characterized using spectral and chemical techniques. The spectral and chemical properties o f the starting material P2VF which were not available in the literature have also been determined. Each o f the above syntheses involved the limitations and difficulties inherent in polymer reactions which had to be eliminated or minimized by judicial use of synthesis techniques. Although the physical propertiies o f the newly synthesized polymers lies outside the scope of this work, especially the P2VF maleican hidrite Diels-Alder adduct (3) and P2VF - asetone cross-linking product (7) deserve careful physical tests for further characterization.
Keywords: Chemistry, Organic.; Heterocyclic compounds.